The Influence of Concentrator Size, Reflective Material and Solar Irradiance on the Parabolic Dish Heat Transfer - Ab Ghani, Mohd Ruddin; Affandi, Rosnani; Gan, Chin Kim; Raman, Siti Hajar; Jano, Zanariah (Indian Society for Education and Environment, 2014)
Concentrating Solar Power (CSP) can meet the clean energy needs for power generation at a cost-competitive rate. Among the CSP technologies, Parabolic Dish (PD) has demonstrated the highest energy conversion efficiency. PD system produces electricity by using solar energy that is transferred from concentrator to receiver, to drive a Stirling engine and the generator. The concentrator in a PD system is used for focusing the solar radiation into the aperture of the receiver that is integrated in the Stirling engine. Stirling engine then converts the absorbed solar energy from the receiver into mechanical power by expanding the working gas in the cylinder. Then, the Stirling engine converts a linear motion into a rotary motion to turn the generator and produce electricity. This study is carried out to analyze the effect of the size, reflecting material and the solar radiation or Direct Normal Irradiance (DNI) to the rate of heat transfer from the concentrator to the receiver in the PD systems. For this purpose, a Matlab Simulink was used, in which the different rate of DNI in George Town, Penang Malaysia were taken into account. The study showed that the rate of heat transfer for the PD systems depended greatly on the size, reflecting material and the DNI of the area. These results are useful to help a better understanding of the relationship between size and reflecting material to the rate of heat transfer for a PD system under different DNI level.